Revealing the Efficacy of Thermostable Biosurfactant in Heavy Metal Bioremediation and Surface Treatment in Vegetables - Ravindran, Amrudha (Front Microbiol, 2020)
Biosurfactants are amphiphilic molecules which showed application in the food, medical, and cosmetics industries and in bioremediation. In this study, a marine sponge-associated bacteria (MSI 54) was identified as a biosurfactant producer which showed high emulsification and surface tension-reducing property. The isolate MSI 54 was identified as Bacillus sp. and the biosurfactant was chemically characterized as a lipopeptide analog based on the spectral data including Fourier transform infrared spectroscopy and nuclear magnetic resonance spectroscopy. The MSI 54 lipopeptide biosurfactant was an anionic molecule which showed high affinity toward cationic heavy metals including Pb, Hg, Mn, and Cd. The heavy metal bioremediation efficacy of the biosurfactant was evaluated using atomic absorption spectroscopy, scanning electron microscopy/energy-dispersive X-ray spectroscopy, and high-resolution transmission electron microscopy analysis. When MSI 54 lipopeptide biosurfactant was added to heavy metals, this resulted in a white co-precipitate of the metal–biosurfactant complex. The heavy metal remediation efficacy of the biosurfactant at a 2.0 × critical micelle concentration (CMC) showed removal of 75.5% Hg, 97.73% Pb, 89.5% Mn, and 99.93% Cd, respectively, in 1,000 ppm of the respective metal solution. The surface treatment of farm fresh cabbage, carrot, and lettuce with 2.0 × CMC of the lipopeptide showed effective removal of the surface heavy metal contaminants.